A Simplified Quantitative Real-Time PCR Assay for Monitoring SARS-CoV-2 Growth in Cell Culture - Christian Shema Mugisha (American Society for Microbiology, 2020)
ABSTRACT Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected millions within just a few months, causing severe respiratory disease and mortality. Assays to monitor SARS-CoV-2 growth in vitro depend on time-consuming and costly RNA extraction steps, hampering progress in basic research and drug development efforts. Here, we developed a simplified quantitative real-time PCR assay that bypasses viral RNA extraction steps and can monitor SARS-CoV-2 growth from a small amount of cell culture supernatants. In addition, we show that this approach is easily adaptable to numerous other RNA and DNA viruses. Using this assay, we screened the activities of a number of compounds that were predicted to alter SARS-CoV-2 entry and replication as well as HIV-1-specific drugs in a proof-of-concept study. We found that E64D (inhibitor of endosomal proteases cathepsin B and L) and apilimod (endosomal trafficking inhibitor) potently decreased the amount of SARS-CoV-2 RNA in cell culture supernatants with minimal cytotoxicity. Surprisingly, we found that the macropinocytosis inhibitor ethylisopropylamiloride (EIPA) similarly decreased SARS-CoV-2 RNA levels in supernatants, suggesting that entry may additionally be mediated by an alternative pathway. HIV-1-specific inhibitors nevirapine (a nonnucleoside reverse transcriptase inhibitor [NNRTI]), amprenavir (a protease inhibitor), and allosteric integrase inhibitor 2 (ALLINI-2) modestly inhibited SARS-CoV-2 replication, albeit the 50% inhibitory concentration (IC50) values were much higher than that required for HIV-1. Taking the data together, this simplified assay will expedite basic SARS-CoV-2 research, be amenable to mid-throughput screening assays (i.e., drug, CRISPR, small interfering RNA [siRNA], etc.), and be applicable to a broad number of RNA and DNA viruses. IMPORTANCE Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of the coronavirus disease 2019 (COVID-19) pandemic, is continuing to cause immense respiratory disease and social and economic disruptions. Conventional assays that monitor SARS-CoV-2 growth in cell culture rely on costly and time-consuming RNA extraction procedures, hampering progress in basic SARS-CoV-2 research and development of effective therapeutics. Here, we developed a simple quantitative real-time PCR assay to monitor SARS-CoV-2 growth in cell culture supernatants that does not necessitate RNA extraction and that is as accurate and sensitive as existing methods. In a proof-of-concept screen, we found that E64D, apilimod, EIPA, and remdesivir can substantially impede SARS-Cov-2 replication, providing novel insight into viral entry and replication mechanisms. In addition, we show that this approach is easily adaptable to numerous other RNA and DNA viruses. This simplified assay will undoubtedly expedite basic SARS-CoV-2 and virology research and be amenable to use in drug screening platforms to identify therapeutics against SARS-CoV-2.